Clinical and Epidemiological Overview of Dysmenorrhea in Ivorian University Campuses of Cocody (Cote d’Ivoire) - Prisca N’Gatta; Dehi Boston Mian; Virginie Angoi; Koffi N’Guessan; Serge Boni (Clinical and Experimental Obstetrics & Gynecology)
Background: Dysmenorrhea is the most common pelvic pain phenomenon during menstruation in women of reproductive age, and is often characterized by social, educational, and economic impact. The objective of the study is to update the epidemiological and clinical characteristics of dysmenorrhea in a university setting, in a low- and middle-income country (LMIC). Methods: A prospective longitudinal descriptive study, over 6 months, conducted in three university residences in Cocody, Abidjan, the capital of Côte d’Ivoire. It involved female students of all levels of study, present at the time of the survey, volunteers and suffering from menstrual pain for more than 12 months, with an intensity higher than 3 on the visual analog scale (VAS). Pain intensity was divided into mild (1–3), moderate (4–5), and severe (7–10) on the VAS. Students with unstable psychological status or with a disability were not included. After obtaining administrative approval from the university, the questionnaire was administered. The parameters studied were general data and specific characteristics of dysmenorrhea. Statistical analysis was performed using EPI INFO 3.5.4 software (Center for disease control and prevention (CDC), Atlanta, GA, USA). Results: The incidence of dysmenorrhea was 79.7%, with an average age of 23.40 years and a median age of 23 years. These students were aged between 20 and 35 (75%), and participated in undergraduate courses (55.8%). The main form of dysmenorrhea was primary (74.2%), the pain location was pelvic (42.3%) or diffuse (53.1%), protomenial (51.2%), severe pain (56.9%), and torsional pain (44.2%), which affects school activities, with an average duration of 3.49 days. Conclusions: Dysmenorrhea is a common disease among women of childbearing age, and due to social and cultural considerations, it may be underdiagnosed in low resources countries. Due to its diverse symptoms, it has a negative impact on the quality of life, leading to a decrease in enrollment rates.